2021
DOI: 10.4253/wjge.v13.i6.189
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of primary aorto-enteric fistulas: A case report and review of literature

Abstract: BACKGROUND Primary aorto-enteric fistula (PAEF) is a rare condition, traditionally treated in the acute, bleeding phase with open surgery or endovascular repair. However, these approaches have high morbidity and mortality, indicating a need for new methods. With advances in endoscopic techniques and equipment, haemoclipping of fistulas has now become feasible. Therefore, we present a systematic review of the English literature and a rare case of a PAEF successfully treated by endoscopic haemoclipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…With advances in endoscopic techniques and equipment, large clips for the closure of vascular-enteric fistulas have come forward. Thus, clipping of fistulas with esophagogastroduodenoscopy has now become feasible, and the clipping of aorta-duodenal fistulas might be the next step forward [19] .…”
Section: Discussionmentioning
confidence: 99%
“…With advances in endoscopic techniques and equipment, large clips for the closure of vascular-enteric fistulas have come forward. Thus, clipping of fistulas with esophagogastroduodenoscopy has now become feasible, and the clipping of aorta-duodenal fistulas might be the next step forward [19] .…”
Section: Discussionmentioning
confidence: 99%
“…11 Endoscopic treatment options to control bleeding have included covered esophageal stents, and 1 study reported the effective use of endoclips to manage AEF. [12][13][14] Such endoscopic interventions may serve as a bridge but may be done as definitive therapy in patients with advanced age, multiple comorbidities, and poor surgical candidates where endoscopic and radiological embolization may be the best alternatives. 15,16 In our case, placement of endoclips did not prevent the massive and lethal bleeding that ensued, reinforcing the need for emergent surgical readiness and intervention in any case of suspected AEF.…”
Section: Discussionmentioning
confidence: 99%